2020
DOI: 10.12681/hnps.2475
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Photon Attenuation Properties of CR-39 Lens

Abstract: The purpose of this study is to investigate photon attenuation parameters of Colombia Resin-39 (CR-39) lens, which are linear attenuation coefficient (LAC), mass attenuation coefficient (MAC), half value layer (HVL), tenth value layer (TVL), mean free path (MFP), effective atomic number (Zeff) and effective electron density (Neff). MACs were determined theoretically and with simulation in the energy range from 0.01 to 105 MeV. Also, obtained MACs of CR-39 lens were compared with MACs of pure aluminum and lead.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…As shown in Figure 8-9, HVLs, TVLs and MFPs increased with increasing photon energy as a function of photon energy. Smaller HVL and TVL indicate a better absorber for radiation shielding [23,25,31]. It has been observed that the difference between the HVL, TVL and MFP values of both lens materials is greater at photon energies less than 0.05 MeV, with the MR-8 lens having relatively higher values in this energy range.…”
Section: Figure2 Uv/vis Absorbance Spectrum Of Nonprescription High-i...mentioning
confidence: 97%
See 1 more Smart Citation
“…As shown in Figure 8-9, HVLs, TVLs and MFPs increased with increasing photon energy as a function of photon energy. Smaller HVL and TVL indicate a better absorber for radiation shielding [23,25,31]. It has been observed that the difference between the HVL, TVL and MFP values of both lens materials is greater at photon energies less than 0.05 MeV, with the MR-8 lens having relatively higher values in this energy range.…”
Section: Figure2 Uv/vis Absorbance Spectrum Of Nonprescription High-i...mentioning
confidence: 97%
“…In addition, two other very important parameters, the radiation protection efficiency (RPE) and the transmission factor (TF), were calculated to determine the effectiveness of shielding material. The equations for all the parameters used in the calculation are given in equation 3-8 [9,[22][23][24][25][26][27][28].…”
Section: Theoretical Calculationsmentioning
confidence: 99%